2011
DOI: 10.1634/theoncologist.2011-0213
|View full text |Cite
|
Sign up to set email alerts
|

Does Obesity Influence the Prognosis of Metastatic Renal Cell Carcinoma in Patients Treated with Vascular Endothelial Growth Factor–Targeted Therapy?

Abstract: Background. Obesity increases the risk for renal cell carcinoma (RCC). However, it has only recently been identified as an independent positive prognostic factor for localized RCC.Objective. To determine whether obesity influences longterm prognosis in metastatic RCC patients receiving vascular endothelial growth factor-targeted therapy.Design, Setting, and Participants. In 116 patients with metastatic RCC who received antiangiogenic agents (sunitinib, sorafenib, axitinib, bevacizumab) in 2005-2010, we evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 13 publications
(14 reference statements)
4
90
2
Order By: Relevance
“…While one study showed that higher than median VFA values were significantly associated with a shorter progression-free survival and OS, the other demonstrated an opposite correlation. 14,15 Finally, greater perirenal fat distance, a proxy of visceral fat, was a significant predictor of ccRCC histopathology in clinical T1a tumours. 29 In the current study, while different obesity measures were significantly associated with hypertension and diabetes, we did not find statistically significant associations between SFA, VFA or VFA% and grade, stage or OS.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…While one study showed that higher than median VFA values were significantly associated with a shorter progression-free survival and OS, the other demonstrated an opposite correlation. 14,15 Finally, greater perirenal fat distance, a proxy of visceral fat, was a significant predictor of ccRCC histopathology in clinical T1a tumours. 29 In the current study, while different obesity measures were significantly associated with hypertension and diabetes, we did not find statistically significant associations between SFA, VFA or VFA% and grade, stage or OS.…”
Section: Discussionmentioning
confidence: 89%
“…4,12 While the reported effects of BMI on RCC have been uniform, reports concerning the effect of visceral adiposity on the pathological and clinical outcomes of RCC are inconsistent. [13][14][15][16][17] Moreover, most previous studies evaluating the predictive value of visceral fat in non-metastatic RCC were conducted among Asian populations, which have relatively lower BMIs than Western populations, and may display a different relationship between BMI and body fat. 18,19 The aim of the current study was to evaluate whether visceral fat area (VFA) and subcutaneous fat area (SFA) were related to tumour characteristics and treatment outcomes in a group of surgically treated, non-metastatic, clear cell RCC (ccRCC) patients from the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Excess adiposity is associated with increased circulating levels of vascular endothelial growth factor, 46 a key regulator of tumor angiogenesis and the main target for bevacizumab antibody therapy; hence, there is a biologic plausibility that obesity might be a potential predictive biomarker in this setting. This has been tested in the settings of metastatic colorectal cancer 47,48 ; metastatic renal cell carcinoma 49,50 ; and advanced ovarian cancer 51 (listed in Table 3). Several of these studies were retrospective, had small sample sizes, lacked controls of conventional treatment arms, and were underpowered to perform tests for interaction; not unexpectedly, the findings are inconsistent.…”
Section: Obesity As a Treatment Effect Modifiermentioning
confidence: 99%
“…However, the lack of effective prognostic prediction markers to stratify the patients remains a major challenge to establish an optimal personalized treatment paradigm of using these antiangiogenic agents to date. In a continuous effort to identify more effective prognostic markers, 'adiposity' has recently attracted research interest as a potential clinical biomarker to evaluate the efficacy of applying VEGF-targeted antiangiogenic therapy to treat a variety of cancers, including colon cancer (7,19), renal cell carcinoma (20,21) and ovarian cancer (9). However, previous studies generated somehow conflicting results (7,19,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…In a continuous effort to identify more effective prognostic markers, 'adiposity' has recently attracted research interest as a potential clinical biomarker to evaluate the efficacy of applying VEGF-targeted antiangiogenic therapy to treat a variety of cancers, including colon cancer (7,19), renal cell carcinoma (20,21) and ovarian cancer (9). However, previous studies generated somehow conflicting results (7,19,20,21). In the present study, a CAD approach was developed for the first time to quantitatively extract adiposity-related image features and to demonstrate the feasibility of applying multivariate data analysis models to stratify EOC patients with and without potential clinical benefit by receiving maintenance bevacizumab-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%